PENYEBAB DAN PELUANG ANAK BERUSIA 7-18 TAHUN BERSEKOLAH TEPAT WAKTU DI PROVINSI NUSA TENGGARA TIMUR TAHUN 2023 - Josephin Natalia Fanggi (Badan Pusat Statistik Provinsi NTT, 2024)
Every Indonesian citizen is required to enhance their education. The Indonesian government has implemented a policy to extend the compulsory basic education program to 12 years. This extension is considered complete if the Gross Enrollment Rate (GER) for primary schools and equivalent, junior high schools and equivalent, and senior high schools and equivalent reaches 100 percent. However, the GER for primary schools and equivalent is 86.59 percent, for junior high schools and equivalent is 75.54 percent, and for senior high schools and equivalent is 70.52 percent in East Nusa Tenggara Province (NTT) for the 2023/2024 academic year, indicating issues in the expansion of access as it has not reached the 100 percent target. This study uses raw data from the 2023 NTT Susenas KOR. The unit of analysis is children aged 7-18 years. The analytical methods used are Descriptive Analysis, Independence Test (Chi-square Test), and Logistic Regression Analysis. The results of the logistic regression analysis, with a significance level (α) of 5 percent, indicate that the variable influencing children aged 7-12 years to attend school on time is the number of household members. Meanwhile, the variables influencing children aged 13-15 years and 16-18 years to attend school on time are the education level of the head of the household and the child's gender.